Early Blockade of EphA4 Pathway Reduces Trigeminal Neuropathic Pain - Kim, Min-Ji (J Pain Res, 2020)
BACKGROUND: Although the Eph receptor plays an important role in the development of neuropathic pain following nerve injury, there has been no evidence of the participation of the ephrin A4 receptor (EphA4) in the development of trigeminal neuropathic pain. The present study investigated the role of EphA4 in central nociceptive processing in rats with inferior alveolar nerve injury. MATERIALS AND METHODS: Male Sprague-Dawley rats were used in all our experiments. A rat model for trigeminal neuropathic pain was produced using malpositioned dental implants. The left mandibular second molar was extracted under anesthesia, followed by the placement of a miniature dental implant to injure the inferior alveolar nerve. RESULTS: Our current findings show that nerve injury induced by malpositioned dental implants evokes significant mechanical allodynia and up-regulation of EphA4 expression in the ipsilateral trigeminal subnucleus caudalis. Although daily treatment with EphA4-Fc, an EphA4 antagonist, did not produce prolonged anti-allodynic effects after the chronic neuropathic pain had been already established, an early treatment protocol with repeated EphA4-Fc administration significantly attenuated mechanical allodynia before initiation of chronic neuropathic pain. Finally, we confirmed the participation of the central EphA4 pathway in the development of trigeminal neuropathic pain by reducing EphA4 expression using EphA4 siRNA. This suppression of EphA4 produced significantly prolonged anti-allodynic effects. CONCLUSION: These results suggest that early blockade of central EphA4 signaling provides a new therapeutic target for the treatment of trigeminal neuropathic pain.